Computed tomography-based evaluation of aortic annulus, prosthesis size and impact on early residual aortic regurgitation after transcatheter aortic valve implantation - Nicola Buzzatti; Francesco Maisano; Azeem Latib; Michela Cioni; Maurizio Taramasso; M. Mussardo; Antonio Colombo; Ottavio Alfieri (2012)
Computed tomography (CT) is an increasingly utilized method for the evaluation of patient suitability for transcatheter aortic valve implantation (TAVI). The aim of this study was to analyse the role of CT in the choice of prosthesis and the prevention of residual aortic regurgitation (RAR).From November 2007 to September 2010, 115 patients (median age 81 years, inter-quantile range (IQR) 76-85; median ejection fraction 55%, IQR 45-60; median logistic EuroSCORE 19.7, IQR 11.0-32.1) undergoing TAVI were evaluated with a pre-procedural CT. An aortic complex was evaluated with multi-planar reconstructions, and we defined significant early RAR as RAR ≥ 2, and prosthesis/annulus mismatch (PAM) as the ratio between prosthesis size and mean annular size. All analyses were conducted for the whole sample and then separately for the two types of prosthesis implanted.An Edwards-SAPIEN(®) prosthesis was implanted in 62 patients (54.7%), and a Medtronic CoreValve(®) in 52 (45.2%). Aortic annulus minimum and maximum diameters were 22.6 ± 2.1 and 26.0 ± 2.3 mm, respectively. The aortic annulus diameter and the length of the free edge of the aortic cusps were linearly related to a 1:1 ratio (P < 0.0001). Significant RAR (34 patients, 30%) appeared directly related to the annulus diameters (particularly maximum and medium diameters, P = 0.0003 and P = 0.0010, respectively) and cusp length (P = 0.0007) but inversely correlated with PAM (P = 0.0006). Prosthesis/annulus oversizing was associated with a reduction in RAR, with a cut-off of 7% as the limit below which RAR increases; moreover, we observed different cut-off values for the Edwards and CoreValve prostheses, although statistical significance was not reached for the CoreValve (respectively, 2% with P < 0.0001, 11% with P = 0.16). No association was found between PAM and possible PAM-related complications.CT evaluation prior to TAVI showed that RAR was directly correlated with aortic root dimensions (particularly maximum and medium annulus diameters and cusp lengths) and inversely correlated with PAM. Oversizing the prosthesis by at least 7% reduces the risk of RAR. CT is an essential and invaluable tool in the assessment of patients undergoing TAVI.